2021
DOI: 10.3390/microorganisms9020441
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Biofilm Activity of Cannabidiol against Candida albicans

Abstract: Candida albicans is a common fungal pathogen in humans. Biofilm formation is an important virulence factor of C. albicans infections. We investigated the ability of the plant-derived cannabidiol (CBD) to inhibit the formation and removal of fungal biofilms. Further, we evaluated its mode of action. Our findings demonstrate that CBD exerts pronounced time-dependent inhibitory effects on biofilm formation as well as disruption of mature biofilm at a concentration range below minimal inhibitory and fungicidal con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 62 publications
1
35
0
Order By: Relevance
“…CBG treatment led to increased ROS levels that might cause oxidative stress in the bacteria. This observation is in accordance with the data observed by Feldman et al [54], demonstrating an increase in ROS production in C. albicans biofilm treated with CBD. Additionally, Singer et al [55] observed that CBD induces robust ROS production when using glioma stem cells.…”
Section: Discussionsupporting
confidence: 94%
“…CBG treatment led to increased ROS levels that might cause oxidative stress in the bacteria. This observation is in accordance with the data observed by Feldman et al [54], demonstrating an increase in ROS production in C. albicans biofilm treated with CBD. Additionally, Singer et al [55] observed that CBD induces robust ROS production when using glioma stem cells.…”
Section: Discussionsupporting
confidence: 94%
“…According to the European Committee on Antimicrobial Susceptibility Testing (EUCAST), the antifungal clinical breakpoints are between 0.001 mg/L and 16 mg/L [ 60 ]. Using EUCAST guidelines in this review, the most active compounds that inhibit (>50%) Candida biofilm formation are lichochalcone A (from 0.2 mg/L) [ 61 ], thymol (from 3.12 mg/L) [ 26 ], dioscin (from 3.9 mg/L) [ 31 ], baicalein (from 4 mg/L) [ 62 ], warburganal (4.5 mg/L) [ 52 ], pterostilbene, waltheriones and riccardin D (both from 8 mg/L) [ 63 , 64 , 65 ], polygodial (10.8 mg/L) [ 52 ], cannabidiol and eugenol (both from 12.5 mg/L) [ 58 , 66 ], and ivalin (15.4 mg/L) [ 67 ]. It is interesting that monotherpenes, which represent the highest percentage of substances listed in Table 2 , are not the most active compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Two hundred microliters of a suspension of C. albicans in RPMI with an optical density (OD) of 0.3 at 600 nm were seeded in 96 flat-bottom transparent wells (Corning) in the presence of increasing concentrations of CTZ or an equivalent concentration of ethanol that served as the control. The OD at 600 nm was measured after a 24 h incubation in Infinite M200PRO plate reader (Tecan, Trading AG, Männedorf, Switzerland) [ 20 ]. The percentage of fungi in the samples was calculated using the following formula: (OD CTZ /OD PL ) × 100, where OD CTZ is the average OD 600 nm of the CTZ-treated samples and OD PL the average OD 600 nm of the control samples.…”
Section: Methodsmentioning
confidence: 99%
“…After 14 days of exposure to C. albicans in the planktonic-based activity assay, the SRV-VPs were washed twice in sterile PBS, and stained with 3.25 µM SYTO 9 green fluorescent nucleic acid stain (Invitrogen, Life Technologies Corporation, Eugene, OR, USA), 2.5 µg/mL propidium iodide (PI; Sigma, St. Louis, MO, USA) and 20 µg/mL AlexaFluor 647 -conjugated ConA (Invitrogen, Life Technologies Corporation, Eugene, OR, USA) for 20 min at room temperature in the dark [ 20 ]. Thereafter, the samples were washed twice in PBS, fixed in 4% paraformaldehyde in PBS for 1 h, and kept in 50% glycerol in DDW until visualizing the biofilms under a spinning disk confocal microscope (Nikon Yokogawa W1 Spinning Disk, Tokyo, Japan, with 50 µm pinholes; SDCM).…”
Section: Methodsmentioning
confidence: 99%